2015
DOI: 10.1002/jemt.22543
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of calcium- and fluoride-containing materials for the remineralization of primary teeth with early enamel lesion

Abstract: The aim of the study was to determine the efficacy of different products containing fluoride, calcium and phosphate for enamel remineralization in eroded primary teeth. A total of 90 sound primary canine teeth were randomly divided into 5 groups of 18 teeth each: 1) control (polished enamel), 2) 5% DuraShield sodium fluoride varnish, 3) 500 ppm fluoridated toothpaste, 4) casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) cream, and 5) Clinpro White varnish containing functionalized tri-calcium phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 26 publications
3
46
0
1
Order By: Relevance
“…Evidence-based review and research studies on the calcium phosphate agent for prevention of tooth caries in children indicated that calcium and phosphate ion promote remineralization of early enamel caries,[37383940414243444546474849] which is in line with the results of this study; however, which type of calcium phosphate compound is the best remineralizing agent is still controversial. [4243444546474849]…”
Section: Discussionsupporting
confidence: 84%
“…Evidence-based review and research studies on the calcium phosphate agent for prevention of tooth caries in children indicated that calcium and phosphate ion promote remineralization of early enamel caries,[37383940414243444546474849] which is in line with the results of this study; however, which type of calcium phosphate compound is the best remineralizing agent is still controversial. [4243444546474849]…”
Section: Discussionsupporting
confidence: 84%
“…Only one study had low risk of bias in blinding of outcome assessment and the rest had unclear risks of bias. Overall, the included studies in vitro had unclear risks of random-sequence generation and allocation concealment [24,[28][29][30][31][32][33][34][35].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…All three studies provided average surface roughness data and were included in the analysis [15,24,31]. When the data from the three studies were pooled, no significant heterogeneity was found (Chi 2 = 2.77, df = 2, P = 0.25, I 2 = 28%).…”
Section: Average Surface Roughness From In Vitro Experimentationmentioning
confidence: 99%
“…relative to the composition of dental enamel [12,14]. Therefore, the change of concentration for both organic and inorganic substances in the oral fluid results in a decrease in the gradient relative to dental biofilm, impacting on the state of the dental enamel health [15][16][17][18]. Consequently, studies of the impact of exogenous and endogenous preventive drugs on the change in the molecular composition of the oral fluid are relevant.…”
Section: +mentioning
confidence: 99%
“…The investigation and comparison of different prevention methods, including fluoridation, will determine which phosphorusand calcium-containing agents promote the recovery of dental enamel [11,15,[19][20][21][22][23]. The prophylactic efficiency of exogenous methods, namely tooth brushing, gel application and laser irradiation, has been demonstrated [20,21,[24][25][26][27][28].…”
Section: +mentioning
confidence: 99%